Kinetic and Mechanistic Study of Oxidative Degradation and Detoxification of Fast Yellow Azo Dye Using Surfactant Assisted Ir-Ni Bimetallic Nanocatalyst - Goel, Anjali; Shikha (Current Organocatalysis, 2022)
Aims: Catalytic degradation of azo dye. Background: Azo dyes are toxic agents and pollutants, and the degradation of these dyes has an important application in the treatment of textile industry wastes.Catalytic decolorization of fast yellow dye by hexacyanoferrate (III), abbreviated as HCF(III) using polyvinylpyrrolidone abbreviated as PVP stabilized Ir-Ni bimetallic nanocrystals has been evaluated by kinetic spectrophotometric method at 440nm wavelength of the reaction mixture. Methods: The impact of various operational factors such as fast yellow dye abbreviated as [FY], oxidant [HCF(III)] ions, promoter iridium-nickel bimetallic nanoparticles abbreviated as [(Ir-Ni)] BMNPs, and solution pH on the rate of the reaction have been examined. Results: The results represent that the reaction follows the first-order kinetics model with respect to [oxidant] at optimum pH 8 and fix temperature 40 ± 0.1°C. Thermodynamic parameters such as activation energy (Ea), enthalpy (ΔH#), entropy (ΔS#), frequency factor (A), and free energy of activation (ΔF#) have been evaluated by examining the reaction rate at four temperatures i.e., 40°C, 45°C, 50°C, and 55°C. On the basis of experimental outcomes, an appropriate mechanism involving complex formation has been proposed. Conclusion: Analytical techniques such as UV-Vis spectroscopy, FTIR, and LCMS of degraded products represent the formation of easier and less harmful compounds.
Keywords: Ir-Ni bimetallic nanoparticles